2006
DOI: 10.1002/anie.200504049
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot, 18‐Component Synthesis of an Octahedral Nanocontainer Molecule

Abstract: A whole in one! The octahedral nanocontainer 3 composed of six cavitands 1 that are connected together by 12 diamino bridging units 2 through 24 imine bonds was synthesized in nearly quantitative yield in a one‐pot reaction. Molecular mechanics calculations and NMR experiments suggest that this container has a diameter of 3.2 Å and an inner cavity volume of about 1700 Å3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
107
1
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(120 citation statements)
references
References 49 publications
2
107
1
2
Order By: Relevance
“…Additional preliminary studies show these kinds of material to have an affinity towards hydrocarbons, a feature we are further exploring. In light of current efforts to synthesize organic-inorganic hybrid molecules with large inner cavities (such as nanocages and molecular containers), [23,24] this new range of porous materials offers exciting opportunities for both fundamental study and potential industrial application.…”
mentioning
confidence: 99%
“…Additional preliminary studies show these kinds of material to have an affinity towards hydrocarbons, a feature we are further exploring. In light of current efforts to synthesize organic-inorganic hybrid molecules with large inner cavities (such as nanocages and molecular containers), [23,24] this new range of porous materials offers exciting opportunities for both fundamental study and potential industrial application.…”
mentioning
confidence: 99%
“…64 In the second example the tetraformyl cavitand 67 was a starting material. It was observed that one-pot reactions of 67 with ethylene 1,2-diamine 68 lead to covalently bound capsules of a different shape, in dependence on the kind of solvent; in THF the tetramer 69, in CHCl 3 the hexamer 70 and in CH 2 Cl 2 the octamer 71 are formed 10,11 .Octamer 71 is a square antiprismatic capsule in which each cavitand occupies one of the eight corners 11 .…”
Section: Methodsmentioning
confidence: 99%
“…Calixarene-based capsules of higher multiplicity are mainly trimeric and hexameric species, albeit tetrameric and octameric compounds are also known. 10,11 An attention is paid now to nanotubes, 12,13 this theme however is not described here.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) (ref. 26). Our approach strongly surpasses earlier multistep covalent synthesis of related nanocontainers in its simplicity and efficiency, which should facilitate applications in medicinal, analytical, chemical and material sciences 27,28 .…”
Section: Introductionmentioning
confidence: 93%